Regiospecific oxidation of polycyclic aromatic phenols to quinones by hypervalent iodine reagents - Wu, Anhui (2010)
The hypervalent iodine reagents o-iodoxybenzoic acid (IBX) and bis(trifluoro-acetoxy)iodobenzene (BTI) are shown to be general reagents for regio-controlled oxidation of polycyclic aromatic phenols (PAPs) to specific isomers (ortho, para, or remote) of polycyclic aromatic quinones (PAQs). The oxidations of a series of PAPs with IBX take place under mild conditions to furnish the corresponding ortho-PAQs. In contrast, oxidations of the same series of PAPs with BTI exhibit variable regiospecificity, affording para-PAQs where structurally feasible and ortho-PAQs or remote PAQ isomers in other cases. The structures of the specific PAQ isomers formed are predictable on the basis of the inherent regioselectivities of the hypervalent iodine reagents in combination with the structural requirements of the phenol precursors. IBX and BTI are recommended as the preferred reagents for regio-controlled oxidation of PAPs to PAQs.